Corn Response Across Plant Densities and Row Configurations for Different Moisture Environments. (5th March 2020) - Balkcom, Kipling S.; Bowen, Kira L.
Abstract : Corn ( Zea mays L.) production in the Southeast can be negatively impacted by erratic summer rainfall and drought-prone, coarse-textured soils, but irrigation combined with conservation tillage and cover crops may support greater plant densities arranged in different row configurations to improve yield. We examined five site-years of data across two soil types in Alabama to compare corn yields in a conservation system across three plant densities for single- and twin-row configurations in dryland and irrigated moisture regimes. Treatments were arranged with a split plot treatment restriction in a RCB design with three replications. Main plots were irrigation level (no irrigation and irrigation), and subplots were a factorial arrangement of three plant densities (5.9, 7.4, and 8.9 plants m −2 ) and row configurations (single and twin). A moisture environment (low and moderate) variable, defined by growing season rainfall, was used to average over site-years. In general, irrigation in the moderate-moisture environment improved each measured variable (plant height, stover yield, corn yield, and test weight) and decreased grain N concentration and aflatoxin levels compared to the low-moisture environment with no irrigation. Benefits of increased rainfall and irrigation to reduce soil moisture stress across drought-prone soils were evident. Pooled results across all site-years indicated no yield response as plant density increased, but greater yields were observed with the greatest plant densities in the moderate-moisture environments. No advantage for twin-row corn production was observed across five site-years in Alabama, which indicates either row configuration can be successfully adopted.